(untitled)
Interfacial solvated electrons (e^-_sol s) possess profound application values in physics, chemistry, and materials, thus attracting ever-growing attention. Although previous studies have unequivocally corroborated the involvement of e^-_sol s in the reaction of alkali metals with water, the mechanism has not been thoroughly revealed. Here, we simulate the solvation and ionization process of a single Na or a metallic Na_8 cluster at the vacuum-liquid interface by the hybrid functional-based ab initio molecular dynamics (AIMD) method, especially to elucidate the interfacial electron dynamics behavior. Results show that the electron donated by Na or Na_8 is partially solvated at the interface, a process driven by both the Na^+ interaction with the electron and its stabilization in water, which promotes electron redistribution, delocalization, and activation. Additionally, solvation increases the H_2O population near HOMO and on unoccupied orbitals, promoting H_2O reorganization and electron transfer. In aqueous solutions, Na is highly ionized and generates a unique pre-solvated electron (e^-_pre ). Na_8 cluster, on the other hand, is partially solvated through bottom active O-coordinating sites at the interface, polarizes internally, and produces a pre-solvated dielectron (e^2-_2 pre ), which is followed by H_2O reorganization near the surface and the subsequent hydrogen evolution reaction by proton-coupled electron transfer. Surrounding H_2O molecules form multiple Na-O bonds with the remaining Na^2+_8 to compensate for e^2-_2 pre loss. Our work displays the microscopic dynamics mechanism of Na and H_2O reaction by AIMD simulation and provides evidence for the participation of e^-_pre s in the hydrogen evolution reaction, which deepens our attention and understanding of redox reactions involving e^-_sol s. , number=1, journal=Communications in Computational Chemistry, year=2025, month=Sept., pages=13–23